2010
DOI: 10.1152/jn.00815.2009
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccade Cost Is Modulated by Contextual Experience of Location Probability

Abstract: Liu C-L, Chiau H-Y, Tseng P, Hung DL, Tzeng OJL, Muggleton NG, Juan C-H. Antisaccade cost is modulated by contextual experience of location probability. J Neurophysiol 103: 1438 -1447, 2010. First published December 23, 2009 doi:10.1152/jn.00815.2009. It is well known that pro-and antisaccades may deploy different cognitive processes. However, the specific reason why antisaccades have longer latencies than prosaccades is still under debate. In three experiments, we studied the factors contributing to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 53 publications
4
38
1
1
Order By: Relevance
“…KristjĂĄnsson et al (2001) found that shifting attention to a secondary task before saccade target onset can interfere with the reflexive prosaccade and consequently allow faster antisaccades. Liu et al (2010) found that spatial probability of saccade locations can also effectively modulate the antisaccade cost. Most important, Olk and Kingstone (2003) found that antisaccade cost can also be altered by changing the way pro-and antisaccade trials are organized.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…KristjĂĄnsson et al (2001) found that shifting attention to a secondary task before saccade target onset can interfere with the reflexive prosaccade and consequently allow faster antisaccades. Liu et al (2010) found that spatial probability of saccade locations can also effectively modulate the antisaccade cost. Most important, Olk and Kingstone (2003) found that antisaccade cost can also be altered by changing the way pro-and antisaccade trials are organized.…”
mentioning
confidence: 98%
“…They found facilitation only in prosaccades to the high-probability location and no effect of probability on antisaccades. Their results suggest that the visual system's sensitivity to probability is not a simple location-and-response coupling, but a process that incorporates task (e.g., saccade type) and location information and other possible events that together provide specific probabilistic contexts (Liu et al 2010). In the present study, we tested whether the visual system can also be sensitive to "events" (e.g., trial type probability in current study) that are intangible but predictive.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have investigated situations in which multiple objects must be tracked and have found that eye gaze is directed more toward the centroid of the target group than to any single target (Fehd & Seiffert, 2008;Huff, Papenmeier, Jahn, & Hesse, 2010) The relationship between attention and eye movements has also been discussed in some literature reviews (Rayner, 2009;Theeuwes, Belopolsky, & Olivers, 2009). Research into visual behavior is motivated by applied psychological questions; the main topics of such research include the processing of facial expressions in social cognition (Brassen, Gamer, Rose, & Buchel, 2010;Domes et al, 2010;Gamer, Zurowski, & Buchel, 2010), the flexibility in the cognitive control of the oculomotor system analyzed in antisaccade paradigms (Liu et al, 2010;Stigchel, Imants, & Richard Ridderinkhof, 2011), and the experimental research of speech processing (Cho & Thompson, 2010;Myung et al, 2010). Eye movement data must undergo a principal processing pipeline including the following modules.…”
Section: Introductionmentioning
confidence: 99%